The Effects of Age, Gene Source and Familial Severity on Factor VIII in Normals and Haemophilia Carriers: Analysis by Multiple Regression - Duncan, Bruce M; Tunbridge, Lynn J; Lloyd, John V (Thrombosis and Haemostasis, 1983)
There are conflicting views on the effects of age, gene source and familial severity on levels of factor VIII in carriers of haemophilia. Different workers have found that factor VIII increases with age, is higher in paternal carriers, and is higher in carriers from families with more severe haemophilia. Other workers have disagreed with these findings. In this study we explored some of the causes of this conflict. We measured factor VIII related antigen and factor VIII coagulant activity on 40 normal females and 48 carriers, and analysed the results by multiple regression and analysis of covariance. Our results indicated that both factor VIII coagulant activity and factor VIII related antigen increased with age, but were unaffected by the familial severity of haemophilia or whether the defective gene came from the mother or the father. We found that the conflicting reports of previous authors were due to high inter-correlations of the studied variables.
Keywords: Factor VIII; Age; Haemophilia; Carriers